PENGARUH SISTEM INFORMASI AKUNTANSI DALAM PELAPORAN KEUANGAN PEMERINTAH DAERAH - Muhammad Hafiz; Suryanto Suryanto; Muhammad Azmii Dalimunthe; Deliana Deliana; Ilham Hidayah Napitupulu (JURNAL MUTIARA AKUNTANSI, 2022)
An accounting information system is an information system that has an information processing process that produces financial reports. This research is causative. The data used in this study were from several previous studies. This study discusses an accounting information system that is able to assist the financial reporting process and an effective system in the financial reporting process.